Pengaruh Edukasi Balut Bidai terhadap Tingkat Pengetahuan Karang Taruna dalam Memberikan Pertolongan Pertama pada Fraktur - Amik Muladi; Fajar Suryo Putro (Universitas Malahayati Lampung, 2025)
ABSTRACT A splint is a tool to maintain the position of a broken bone. A splint is used as a temporary relief and treatment measure before a fractured bone victim receives full medical or paramedical treatment. This research aims to determine the effect of splint dressing health education on the level of knowledge of youth organizations in providing first aid for broken bones. This research design uses a pre-experimental design with a group pre-post-test design approach. This research population only consists of members of the RW 10 Youth Organization, Jungke Village, Karanganyar Regency. The sample for this study consisted of 36 members of youth organizations who had never attended splint dressing education. The sample was taken by purposive sampling. The measurement tool uses a splint dressing knowledge questionnaire, with slides and videos, and data analysis using the Paired T-Test. The study showed that after receiving splint dressing education, of the 36 respondents with more or less knowledge, 1 (2.8%) was in the poor knowledge category, and more respondents were in the good knowledge category. The knowledge category is in the